The Fundamental Metaphor of Sophistry - Tatiane Silva; Marcus Vinicius Cunha (Universidade Federal do Rio Grande do Sul, 2022)
This paper analyzes the metaphor as a discursive strategy to explain and disseminate the concepts that support doctrines in general and educational doctrines in particular. It examines the Cultivation metaphor as a fundamental metaphor for education, as well as its supposed origin in Sophistry, and proposes to replace it with the Navigation metaphor. This substitution makes it possible to assign new meanings both to the practice of the sophists and to the profession of educating today and throughout history, imposing challenges on the training and continuing education of teachers.